Mitigation techniques for voltage SAG in power distribution system by using dynamic voltage restorer / Muhammad Salman Sahak - Sahak, Muhammad Salman (2010)
In power quality, voltage sag is the one of the problem issue in the power distribution system and Dynamic voltage Restorer (DVR) is used for mitigation of the sag problem. Voltage sags are normally caused by switching factors or faults at the transmission line. The fault can be occurring in terms of balance and unbalanced fault. Unbalance fault sag are commonly occur in the distribution system while the balance faults often seen as the worst case and however it seldom occurs. Since voltage sag is creating worse affect, the researches almost keen to find the solution for this problem. According to this problem an effective devices has been designed in order to mitigate the voltage sag problems. Nowadays, a lot of devices have been developed to mitigate voltage sag such as Dynamic Voltage Restorer (DVR), Voltage Dip Compensator (VDC), and Voltage Dip Proofing Inverter (DIP). In this study, focus is given only on the DVR system that will be simulated by using MATLAB SIMULINK software in order to mitigate and overcome the immunization of the sag problem that is occurred by the faults. This device will be connected in series to the problem circuit and it will improve the problem of the sag. At the same time simple calculation for voltage sag and voltage injection by DVR system also described. Finally the DVR system also will improved by increasing the value of MVA rating and secondary transformer in certain specific condition as to ensure that this device has more opportunity to mitigate voltage sag in long duration. The increasing of the capability of DVR also is very important for future development in order to analyze the impact of the DVR to the power distribution system.